THE EXPRESSION OF DEVOTION IN CALLIGRAPHY PAINTINGS - Harissman Harissman; Martwan Martwan (Ekspresi Seni : Jurnal Ilmu Pengetahuan dan Karya Seni, 2019)
The forms of calligraphy paintings was expression of philosophical values of taqwa, it reflected the content of the holy Qur'an and giving the deep guidance of the importance of having attitude, behaviour and norms in a social life of human being. "Taqwa is being obeyed to all of Allah regulations cause of the light that comes from Allah almighty and he expects the reward from Allah and he leaves all the sins activities cause of the light of Allah and he fears of the torture from Allah". The method approach that used in this research were exploration, design and execution of the art work, which had previously been done through literature studies, empirical studies and field studies. The creation of calligraphy painting took from the translation of the holy Qur'an by surah Ali Imran verse 102 that stated "O you who believe, fear Allah truly in His piety; and do not ever die except in a Muslim situation. Calligraphy painting was a bridging of taqwa’s values as an expression to public.